Pengukuran Radiasi Elektromagnetik pada Extremely Low Frequency (ELF) di Lingkungan Universitas Palangka Raya - Adelia, Kadek Ayu Cintya; Kurniati, Ety (Universitas Pahlawan Tuanku Tambusai, 2024)
Electromagnetic wave radiation has a very broad spectrum, ranging from extreme low to very high frequencies. Radiation measurements were carried out with the aim of determining exposure to electromagnetic radiation around Palangka Raya University. From the measurement results, it can be seen that the highest intensity of electromagnetic radiation is in the PPIIG building, namely 80 µT, this is due to the influence of the large voltage around the electricity pole. However, this value still meets the ICNIRP quality standards for magnetic field radiation for the general public. Prolonged exposure to electromagnetic radiation can affect the condition of the body. If you are exposed to radiation for too long, the first thing you will feel is nausea and dizziness. The aim of this research is to provide information for the academic community to better understand and minimize the impacts that occur due to radiation exposure in the campus environment and the basis for health policies for the academic community.